Jejunal perforated gastrointestinal stromal tumor as a rare cause of acute abdomen: case report and review of literature - Medellin, Rito J.; Verastegui, Guillermo J.; Angel, Aylin M. D.; Rodriguez, Antonio (International Journal of Research in Medical Sciences, 2025)
Gastrointestinal stromal tumors (GIST) are the most common mesenchymal tumor of the GI tract. Most cases are asymptomatic, or present as an abdominal mass. Less frequently, they can present as an upper GI bleed or acute abdomen. We hereby present the case of a 47-year-old male who visits the ER department complaining of abdominal pain and melena, with physical exploration findings of acute abdomen. An abdominal computed tomography (CT) scan was performed, where a free intra-abdominal fluid was seen in left upper quadrant and a tumor like mass was detected in small intestine causing bowel obstruction for which he underwent exploratory laparotomy, finding a perforated jejunal GIST. An emergency exploratory laparotomy was performed due to the clinical findings of acute abdomen, upon organ examination, hemoperitoneum was found and intestinal leakage due to a mass in a segment of jejunum 25 cm from Treitz angle, an intestinal resection and anastomosis was performed. GISTs are common tumors that rarely present to the emergency room as an acute abdomen. It is important to the surgeon to bear this in mind and have knowledge of the specifics of management of these type of patients to provide an adequate surgical resection and postoperative risk specific follow up.